Optimization of Tissue Culture Media Inducing Essential Oil Production of Levander (Lavandula angustifolia) - Tuman, C.Büşra; Ayan, Alp; MERİÇ, SİNAN; ATAK, ÇİMEN (My University, 2019)
Aim of this study is to induce in Vitro tissue cultures of levander which produces essential oils which have medical and aromatic properties. Media requirements were investigated for germination, shoot induction and development, rooting, callus initiation and suspenson culture induction. 1 mg/L BAP supplemented MS media presented the highest germination rate by 64.7 % and 2 mg/L BAP supplemented MS media initiated shoot propagation by 95.6 %. For rooting, MS media is supplemented with various NAA and IBA concentrations. The highest rooting rate was observed in 1.25 mg/L IBA supplemented MS media by 60 %. For callus induction MS media was supplemented with various concentrations of IAA, BAP and 2,4-D. The most efficient callus induction media for further suspension culteres was determined as 2 mg/L 2,4-D and 2 mg/L BAP supplemented MS media by 66 %. Characteristic blue pigmentation in suspension cultures were also evaluated spectroscopically. IAA supplemented MS media increased pigmentation significantly.Essential oil contents of suspension cultures were purified by steam destilation method and chacterized by fourier trasport infra red (FTIR) spectroscopy.
Keywords: Micropropagation; Levander; FTIR; Suspension Cultures